2015
DOI: 10.1371/journal.pone.0122928
|View full text |Cite
|
Sign up to set email alerts
|

GeneSippr: A Rapid Whole-Genome Approach for the Identification and Characterization of Foodborne Pathogens such as Priority Shiga Toxigenic Escherichia coli

Abstract: The timely identification and characterization of foodborne bacteria for risk assessment purposes is a key operation in outbreak investigations. Current methods require several days and/or provide low-resolution characterization. Here we describe a whole-genome-sequencing (WGS) approach (GeneSippr) enabling same-day identification of colony isolates recovered from investigative food samples. The identification of colonies of priority Shiga-toxigenic Escherichia coli (STEC) (i.e., serogroups O26, O45, O103, O11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…Completion of these typing tests (including PFGE, MLST, PCR, and serotyping) would generally take Ͼ5 days, while WGS can provide analogous data in 3 days (120). In the latter scenario, a novel approach is used to interpret data during an ongoing Illumina MiSeq run and can correctly identify virulence genes in STEC only 4.5 h after the sequencing run is started (121). Studies that compare routine virulence gene typing with WGS and in silico typing have found that the two methods produce almost identical results (Ͼ90% concordance) (120,122).…”
Section: E Colimentioning
confidence: 99%
“…Completion of these typing tests (including PFGE, MLST, PCR, and serotyping) would generally take Ͼ5 days, while WGS can provide analogous data in 3 days (120). In the latter scenario, a novel approach is used to interpret data during an ongoing Illumina MiSeq run and can correctly identify virulence genes in STEC only 4.5 h after the sequencing run is started (121). Studies that compare routine virulence gene typing with WGS and in silico typing have found that the two methods produce almost identical results (Ͼ90% concordance) (120,122).…”
Section: E Colimentioning
confidence: 99%
“…and Salmonella spp. (Lambert et al, 2015;Clark et al, 2016;Jackson et al, 2016;Wilson et al, 2016). Furthermore, WGS has the potential to discriminate between sporadic and outbreak isolates which may be indistinguishable by current methods of subtyping (Phillips et al, 2016).…”
Section: Whole Genome Sequencingmentioning
confidence: 99%
“…Extracting certain feature classes can be achieved using specialized Web-accessible databases such as the multiple "Finder" applications on the Center for Genomic Epidemiology website (ResFinder [31], VirulenceFinder [199], PathogenFinder [202]), PHAST (156) to search for integrated prophage, and CARD to identifiy antimicrobial resistance genes (203). The latter programs require assembled contigs or annotations as input; however, recently developed tools such as GeneSippr and SRST2 identify gene markers using a mapping approach from quality-filtered sequence reads as input instead of assembled contigs (204,205).…”
Section: Bacterial Typingmentioning
confidence: 99%